If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(x + 6) + 150 = 22 + 20 Reorder the terms: -9(6 + x) + 150 = 22 + 20 (6 * -9 + x * -9) + 150 = 22 + 20 (-54 + -9x) + 150 = 22 + 20 Reorder the terms: -54 + 150 + -9x = 22 + 20 Combine like terms: -54 + 150 = 96 96 + -9x = 22 + 20 Combine like terms: 22 + 20 = 42 96 + -9x = 42 Solving 96 + -9x = 42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-96' to each side of the equation. 96 + -96 + -9x = 42 + -96 Combine like terms: 96 + -96 = 0 0 + -9x = 42 + -96 -9x = 42 + -96 Combine like terms: 42 + -96 = -54 -9x = -54 Divide each side by '-9'. x = 6 Simplifying x = 6
| -7=4+x3 | | 45+15+0.25x=y | | 4(x-5)-7=32x-139 | | 3y^2-8=13 | | 2+y-1=0 | | 2+y+1=0 | | 3(6y+2)+13=5(3y-1)-3 | | 0.02+0.01(5000-x)=84 | | 19-(x+7)=4x-8 | | (19x-8)(6x+7)= | | e^7x+7=4 | | (x-4)(x-7) | | (x-3)(x-10)=-10 | | 5n-6=11 | | (19x-8)X(6x+7)= | | (x-9)(x-7) | | 80+5x/6+x=6 | | 3x=14.4 | | 4(5y+4)-2=2(2y-4)+18 | | 4(2x-3)=-1x-5 | | 43/4-24/5 | | x^2-25x+36=0 | | 4a+3=1 | | 3(5x+1)=-2x-7 | | -5(x+9)-44=1-55 | | 42/3-24/5 | | 6(x-3)+7=2(x-6) | | 5(x-6)+2=6(x-8) | | 6(-1.67)-7y=17 | | x/-7=-2-(-3) | | -2y+2(-6y+6)=8-9(7-y) | | 3(w+12)0 |